Respuesta :
Answer:
3x-18
Step-by-step explanation:
To expand this you must use the distributive property to distribute the 3. Using this property you can multiply the x and -6 by 3. So the expanded equation would first look like x*3 + -6*3. Then simplify to get 3x-18.
Answer:
3x-18 expanded
Step-by-step explanation:
x-6 simplified
use the distributive property to expand the expression
3*x= 3x
3*-6=-18
to simplify,
find the GCF and solve
gcf= 3
3x/3=1x or just x
-18/3=-6
hope this helps
please mark brainliest